Electrolyte-assisted hydrothermal synthesis of holey graphene films for all-solid-state supercapacitors. Issue 24 (4th June 2018) - Liu, Daoqing; Li, Qianwei; Zhao, Huazhang
Abstract : Fabrication of holey reduced graphene oxide films with oxygen-containing groups and their application for all-solid-state supercapacitors. Abstract : A novel strategy was presented for the synthesis of graphene-based film electrodes by electrolyte-induced hydrothermal reduction of holey graphene oxide based films. After hydrothermal treatment, the reduced holey graphene films (rHGFs) maintained their flexibility, integrity and porosity, which resulted from the electrolyte-induced balance between electrostatic repulsion and π–π attraction. The trapped electrolyte (H2 SO4 ) between graphene layers can prevent aggregation, and the resulting supercapacitor exhibits a high specific capacitance in the sulfuric acid electrolyte. Benefitting from the in-plane pores and oxygen-containing groups on graphene sheets, the rHGF electrode exhibits a high specific capacitance of 260 F g −1 (297 F cm −3 ) with remarkable rate performance in a three-electrode system. To evaluate the practical application, flexible all-solid-state supercapacitors based on the rHGF electrode with PVA/H2 SO4 gel electrolyte were prepared, and the device exhibits remarkable cycling stability. The areal capacitance and volumetric energy density were 56 mF cm −2 and 1.41 W h cm −3, respectively. This work demonstrated a cost-effective and simple technique to prepare compact graphene films with continuous ion channels and showed great importance on the design of flexible, portable and highly integrated supercapacitors.